Role of navigation system in functional endoscopic sinus surgery - Agrawal, Manish; Arya, Pooja; Meghwal, Deepchand; Samor, Vivek; Gupta, Gaurav; Kumar, Vijay (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Functional endoscopic sinus surgery (FESS) is a challenging procedure for otorhinolaryngologists. Navigation can reassure the surgeon’s judgement and enhance surgical performance and prevent complication. The study done with aim of comparison between FESS with navigation and conventional FESS and explore other indication of navigation in endoscopic sinus surgery in difficult clinical scenario. Methods: This is a cross-sectional study on patients with sino-nasal disease. 100 patients in whom the ability to identify surgical site is assumed to be compromised by various conditions like previous surgery, massive/ recurrent polyposis, front oethmoidal mucocele, frontal, sphenoid sinus disease were included in the study. Patients were randomly allocated into two groups, group A (50 patients) FESS with navigation and group B (50 patients) conventional FESS. Pre-operative preparation time, intraoperative time, blood loss (Fromme–Boezzaart scoring), surgeon satisfaction, patient satisfaction (SNOT-20), complications were documented on a preformed, pretested proforma. Equipments used were –StealthStation S7 system, CD for recording intraoperative findings. Results: Preoperative preparation time duration was applicable for group A only. Intraoperative time was slightly and insignificantly higher in group A. Blood loss according to Fromme-Boezzaart scoring had lesser scoring values in group A and difference among gradings was statistically insignificant. Surgeons satisfaction and confidence was statistically significant higher in group A. The SNOT-20 score values were lower and insignificant in group A. Conclusions: FESS with navigation is more convenient to surgeon, appears to be safer tool.